Effects of local clay pot and freezer preservation methods on beef quality attribute (2014)
This study was carried out to investigate the influence of local clay pot and freezer preservation on quality properties of fresh beef. 30 clay pots were moulded. 6kg of beef was purchased from Ayetoro abattoir and divided into two portions of 3kg wrapped’in banana leaves and each portion constituted a treatment; T1 = Freezer, T2 = Clay pot. The clay pots were sealed containing 100g of beef each and heated on charcoal fire for 1 hour daily, while beef preserved in freezer was divided into 30 parts of 100g and frozen at -18˚C. Physicochemical, microbiological and sensory properties of preserved beef were determined at 0, 7, 14, 21 and 28 days. Data collected were analysed with ANOVA at p = 0.05. Beef in T1 had higher colour score and lower (p<0.05) shear force values, while beef in T2 had higher yield and lower thermal shortening, protein, ash and TBA were higher in beef preserved with T2 while moisture and fat were higher in T1 beef. Microbial load were higher in T1 as well as colour, tenderness- and texture. However, flavour, odour and acceptability were higher in T2. All properties of preserved beef with the exception of cooking loss, thermal shortening, ash, Thiobarbituric Acid (TBA.,, Total Colifomi Count (TCC) and Total Anaerobic Count (TAG) increased as the time of preservation increased. It is suggested that local clay pot be used by those in developing countries where power supply is still epileptic especially in rural areas, and that beef may not be preserved beyond 14 days since beef properties decreased after that period in this study.